Imputing HbA1c from capillary blood glucose levels in patients with type 2 diabetes in Sri Lanka: a cross-sectional study. Issue 7 (19th July 2020) - Choo, Monica; Hoy, Gregory E.; Dugan, Sarah P.; McEwen, Laura N.; Gunaratnam, Naresh; Wyckoff, Jennifer; Jeevaraaj, Thangarasa; Saththiyaseelan, Arunachalam; Ganeikabahu, B.; Katulanda, Prasad; Balis, Ulysses; Herman, William H.; et al.
Abstract : Objective: To develop a population-specific methodology for estimating glycaemic control that optimises resource allocation for patients with diabetes in rural Sri Lanka. Design: Cross-sectional study. Setting: Trincomalee, Sri Lanka. Participants: Patients with non-insulin-treated type 2 diabetes (n=220) from three hospitals in Trincomalee, Sri Lanka. Outcome measure: Cross-validation was used to build and validate linear regression models to identify predictors of haemoglobin A1c (HbA1c). Validation of models that regress HbA1c on known determinants of glycaemic control was thus the major outcome. These models were then used to devise an algorithm for categorising the patients based on estimated levels of glycaemic control. Results: Time since last oral intake other than water and capillary blood glucose were the statistically significant predictors of HbA1c and thus included in the final models. In order to minimise type II error (misclassifying a high-risk individual as low-risk or moderate-risk), an algorithm for interpreting estimated glycaemic control was created. With this algorithm, 97.2% of the diabetic patients with HbA1c ≥9.0% were correctly identified. Conclusions: Our calibrated algorithm represents a highly sensitive approach for detecting patients with high-risk diabetes while optimising the allocation of HbA1c testing. Implementation of these methods will optimise the usage of resources devoted to the management of diabetes in Trincomalee, Sri Lanka. Further external validation with diverse patient populations is required before applying our algorithm more widely.